Integrating Pharmacokinetics Study, Network Analysis, and Experimental Validation to Uncover the Mechanism of Qiliqiangxin Capsule Against Chronic Heart Failure - Zhang, Yu; Zhu, Mingdan; Zhang, Fugeng; Zhang, Shaoqiang; Du, Wuxun; Xiao, Xuefeng (Frontiers in Pharmacology, 2019)
Objectives: The purpose of this study was to propose an integrated strategy for investigating the mechanism of Qiliqiangxin capsule (QLQX) to treat chronic heart failure (CHF). Methods: Pharmacokinetics analysis was performed to screen the active components of QLQX using high-performance liquid chromatography-tandem mass spectrometry techniques. We then constructed the component-target network between the targets of active components in QLQX and CHF using Cytoscape. A network analysis, including topological parameters, clustering, and pathway enrichment, was established to identify the hub targets and pathways. Finally, some of the predicted hub targets were validated experimentally in Human Cardiac Microvascular Endothelial Cell (HCMEC). Results: We identified 29 active components in QLQX, and 120 consensus potential targets were determined by the pharmacokinetics analysis and network pharmacology approach. Further network analysis indicated that six target genes, namely, VEGFA, CYP1A1, CYP2B6, ATP1A1, STAT3, and STAT4, and ten predicted functional genes, namely, KDR, FLT1, NRP2, JAK2, EGFR, IL-6, AHR, ATP1B1, JAK1, and HIF1A, may be the primary targets regulated by QLQX for the treatment of CHF. Among these targets, VEGFA, IL-6, p-STAT3, and p-JAK2 were selected for validation in the HCMEC. The results indicated that QLQX may inhibit inflammatory processes and promote angiogenesis in CHF via the JAK/STAT signaling pathway. Conclusion: This study provides a strategy for understanding the mechanism of QLQX against CHF by combining pharmacokinetics study, network pharmacology, and experimental validation.